Toward a Risk-Based Oversight Blueprint for Zakat: Integrating Shariah Governance, Three-Lines Assurance, and Proportionate GovTech in Indonesia - Andi Setyo Pambudi (PT. Global Pustaka Imiah, 2026)
Zakat governance in Indonesia continues to face a significant gap between its vast potential and actual performance, reflected in disparities in collection and distribution outcomes, inconsistent reporting practices, and emerging risks associated with uneven digital transformation. These challenges are further intensified by increasing public demands for transparency, the involvement of multiple supervisory actors, and growing exposure to information technology and data-related risks. This study aims to identify the principal weaknesses and risk dimensions of zakat governance oversight, examine risk-based supervisory practices from selected Muslim-majority jurisdictions, and formulate a contextualized Risk-Based Supervision (RBS) framework for Indonesia. Using a qualitative approach based on an integrative literature review, data were collected from academic publications, policy reports, regulatory documents, and institutional records and analyzed through thematic synthesis. The findings reveal four interrelated governance weaknesses, namely regulatory and institutional limitations, weaknesses in supervisory processes, challenges in digital and data governance, and deficiencies in performance and risk measurement. These weaknesses generate five key risk dimensions: governance and compliance, shariah, operations, information technology and data, and reputation. Comparative analysis indicates that effective zakat oversight is characterized by continuous shariah auditing, proportionate supervision based on institutional risk profiles, and digital governance supported by robust data-management systems. The study proposes an integrated RBS model that combines shariah governance, three-lines assurance, GovTech-enabled supervision, and risk-based performance indicators. It recommends establishing national supervisory standards, strengthening the role of Sharia Supervisory Boards, developing interoperable data infrastructures, and implementing a phased reform roadmap to improve accountability, transparency, and the welfare impact of zakat distribution in Indonesia.